Stimulus novelty, task demands, and strategy use in episodic memory - Waris Otto; Fellman Daniel; Jylkkä Jussi; Laine Matti (United Kingdom, 2022)
Cognitive task performance is a dynamic process that evolves over time, starting from the first encounters with a task. An important aspect of these task dynamics is the employment of strategies to support successful performance and task acquisition. Focusing on episodic memory performance, we: (1) tested two hypotheses on the effects of novelty and task difficulty on strategy use; (2) replicated our previous results regarding strategy use in a novel memory task; and (3) evaluated whether repeated open-ended strategy queries affect task performance and/or strategy use. The present pre-registered online study comprised 161 adult participants who were recruited through the Prolific crowdsourcing platform. We employed two separate 5-block list learning tasks, one with 10 pseudowords and the other with 18 common nouns, and collected recall performance and strategy reports for each block. Using Bayesian linear mixed effects models, the present findings (1) provide some support for the hypothesis that task-initial strategy development is not triggered only by task novelty, but can appear also in a familiar, moderately demanding task; (2) replicate earlier findings from an adaptive working memory task indicating strategy use from the beginning of a task, associations between strategy use and objective task performance, and only modest agreement between open-ended vs. list-based strategy reports; and (3) indicate that repeated open-ended strategy reports do not affect objective recall. We conclude that strategy use is an important aspect of memory performance right from the start of a task, and it undergoes development at the initial stages depending on task characteristics. In a larger perspective, the present results concur with the views of skill learning and adaptivity in cognitive task performance.